Research on the evaluation model of ecological environment change and its internal driving mechanisms - Rui Xu; Junfeng Deng; Youshan He; Guochen Sui; Xunchang Li; Wei Yang (Geomatics, Natural Hazards & Risk, 2024)
The primary objective of this paper is to delve into the underlying driving forces behind changes in the ecological environment. To achieve this, the paper not only analyzes the multifaceted social, economic, and natural aspects of the composite ecosystem but also develops an ecological environment change evaluation model employing the topological hierarchy-entropy weight method. This model serves as a valuable tool for assessing trends and determining the drivers of ecological change. As a case study, the paper focuses on Gaoqiao Town, located in Yan’an City, Shaanxi Province. It involves a meticulous process of processing multi-year remote sensing images of the study area,as well as image cropping to extract and decode natural index data. Additionally, the paper utilizes social and economic data alongside survey data from annual reports published by local governments within the study area. These datasets are then subjected to the proposed model to evaluate ecological changes in the region. The results show that the modelling approach introduced in this paper effectively captures the ecological changes and their underlying causes in the selected areas, and can provide valuable references for government departments to formulate wise ecological environmental protection and management policies.